THE SIGNIFICANCE OF MODERN PEDAGOGICAL TERMS AND METACOGNITIVE SKILLS IN THE EDUCATIONAL PROCESS (Eureka Journal of Education & Learning Technologies, 2026)
This article explores the theoretical underpinnings of emerging pedagogical concepts in contemporary education, with a particular focus on self-regulated learning, reflective practice, and critical thinking. Considerable emphasis is placed on examining the nature, structural elements, and functional role of metacognitive skills within the learning environment. The core components of metacognition — namely planning, self-monitoring, and evaluation — are analyzed through a scientific lens, and their contribution to building the professional competencies of prospective educators is thoroughly discussed. The study concludes that the systematic integration of a metacognitive approach into everyday educational practice is not only beneficial but essential.
Keywords: Metacognitive skills, metacognition, self-regulated learning, reflection, critical thinking, pedagogical innovation, professional competence, educational effectiveness.